2015
DOI: 10.1097/qad.0000000000000837
|View full text |Cite
|
Sign up to set email alerts
|

Re-engagement in HIV care among mothers living with HIV in South Africa over 36 months post-birth

Abstract: Summary PMTCT services are integrated into antenatal care in South Africa, but post-birth care is at HIV clinics. Almost all Mothers Living with HIV (MLH) in 24 township neighborhoods (N=324) reported engagement in HIV care from pregnancy to 36 months post-birth. Less than half re-engaged in HIV care at 6 months (45%), 52.5% at 18 months, and 62.5% at 36 months. Most were prescribed ARVs if reengaged in care, yet only about half (53%) are on ARVs at 36 months post birth. Implementation of Option B+ will requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Perhaps, due to their HIV, MLH are more engaged with the health care system and take children to the hospital with less severe symptoms. However, in a related publication (49), we have shown that MLH only slowly reengage in HIV care following childbirth. By three years post-birth, only 62% of MLH have reengaged in health care.…”
Section: Discussionmentioning
confidence: 82%
“…Perhaps, due to their HIV, MLH are more engaged with the health care system and take children to the hospital with less severe symptoms. However, in a related publication (49), we have shown that MLH only slowly reengage in HIV care following childbirth. By three years post-birth, only 62% of MLH have reengaged in health care.…”
Section: Discussionmentioning
confidence: 82%
“…However, most of this attrition occurred by six months of age. Similarly, there is evidence that the immediate postpartum period is also a time of increased risk for attrition among HIV‐positive mothers . This suggests that the first six months of postpartum follow‐up might represent an especially vulnerable period, and that interventions to mitigate attrition or promote retention of mother‐infant pairs might have a greater impact if focused on and implemented early in the EID cascade.…”
Section: Discussionmentioning
confidence: 99%
“…14 Despite this astounding achievement, there is mounting evidence that women who initiate ART during pregnancy may be at very high risk of LTFU, 15–18 with re-engagement in routine HIV care after delivery a particular concern. 19,20 Suggested reasons for this high LTFU include a lack of perception of need for treatment, 16,21 increased financial burden, 16,22 and stigma. 23–26 In our recent work, we have observed that HIV-positive women reported difficulty in providing a “valid reason” to be seen at a clinic after giving birth; while pregnant, clinic attendance is accepted, but after delivery, clinic attendance and medication adherence are viewed with societal and familial suspicion.…”
Section: Introductionmentioning
confidence: 99%